National survey of referrals for precocious puberty in Germany - Joachim Woelfle; Dirk Schnabel; Bettina Gohlke; Sonja Baehr; Felix Schreiner (BMJ Publishing Group, 2023)
An unusual high number of girls were referred to our paediatric endocrine clinic with suspected precocious puberty (PP) since the beginning of the COVID-19 pandemic. We analysed our data and initiated a survey among German paediatric endocrinologists.At our centre, less than 10 patients were diagnosed of PP annually between 2015 and 2019. This increased to n=23 (2020) and n=30 (2021). A German survey confirmed this observation: Out of 44 centres which completed the questionnaire, 30/44 (68%) reported an increase of PP. Above this, 32/44 (72%) stated an increase in girls diagnosed with 'early normal puberty' since the beginning of the COVID-19 pandemic.